2018
DOI: 10.3390/ma12010117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recrystallization Annealing on Corrosion Behavior of Ta-4%W Alloy

Abstract: The effect of recrystallization annealing on corrosion behavior of Ta-4%W alloy was studied. It is found that the deformed sample contains high dense dislocations and dislocation boundaries. During annealing, these dislocations and dislocation boundaries are replaced by recrystallizing grains until the alloy is fully recrystallized. Both the anodic dissolution and the cathodic activity is much more blocked. The corrosion potential gradual shift towards negative values and corrosion current density decrease, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…However, lowering the grain boundary energy by the recovery treatment enhanced the corrosion resistance. The sharpened grain boundaries in a more stable state also increase hardness by more effectively blocking the movement of dislocations across the grain boundaries and thus elevated wear resistance, [36,[45][46][47][48][49][50][51][52][53][54] which has also been demonstrated by the results reported in this article. It should be pointed out that if the annealing temperature is sufficiently high, resulting in recrystallization and grain growth, the mechanical strength will be reduced.…”
Section: Microstructural Variation and Its Influence On Properties Of...supporting
confidence: 75%
See 2 more Smart Citations
“…However, lowering the grain boundary energy by the recovery treatment enhanced the corrosion resistance. The sharpened grain boundaries in a more stable state also increase hardness by more effectively blocking the movement of dislocations across the grain boundaries and thus elevated wear resistance, [36,[45][46][47][48][49][50][51][52][53][54] which has also been demonstrated by the results reported in this article. It should be pointed out that if the annealing temperature is sufficiently high, resulting in recrystallization and grain growth, the mechanical strength will be reduced.…”
Section: Microstructural Variation and Its Influence On Properties Of...supporting
confidence: 75%
“…Such a reduction of dislocation density benefits the corrosion resistance as demonstrated in this study and previous ones reported in the literature. [ 36,50,51 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Craniomaxillofacial surgery implant materials, including medical metals, inorganic nonmetals, polymers, and composite materials, etc., have become an important part of clinical treatment. Tantalum metal has excellent corrosion resistance as well as high melting point, high strength, and wear resistance 4 . Recent studies have shown that tantalum is more biocompatible than titanium 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The question still remains therefore how the change in corrosion resistance relates to the severe deformation structure for metals and alloys. In our previous studies on the Ta-4%W alloy [ 26 , 27 , 28 , 29 , 30 ], we have reported the microstructural evolution after cold rolling and the corrosion behavior on rolling plane in sulfuric acid. However, the effects of macroscopic orientation and crystallographic texture in different directions on the surface dissolution of cold-rolled sheets are still unknown and they are the key components of the present research.…”
Section: Introductionmentioning
confidence: 99%